2002
DOI: 10.1590/s0100-204x2002001100015
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento de espécies herbáceas em misturas de solo com diferentes graus de contaminação com metais pesados

Abstract: O objetivo deste trabalho foi avaliar, em casa de vegetação, o comportamento de espécies herbáceas em relação ao excesso de Cd e Zn no solo. O gradiente de contaminação foi estabelecido a partir de mistura de solo contaminado com solo sem contaminação em diferentes proporções. As sementes foram semeadas em tubetes contendo 250 mL de solo, e após 90 dias as plantas foram colhidas e avaliadas. A maioria das espécies apresentou redução no crescimento com aumento da contaminação do solo e elevadas concentrações de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
6
14
0
14
Order By: Relevance
“…In conclusion, our results demonstrated that Pfaffia glomerata has great potential for use in Cd-phytoextraction programs, being a Cdhyperaccumulator species, as previous proposed by Carneiro et al (2002). The high Cd-tolerance of this species is closely related to anatomical and physiological features, including endodermal thickness, stomatal size and number, root SOD and GPX activities, and leaf GPX and CAT activities can serve as Cd-tolerance markers for this species.…”
Section: Antioxidant Enzyme Activitiessupporting
confidence: 82%
See 4 more Smart Citations
“…In conclusion, our results demonstrated that Pfaffia glomerata has great potential for use in Cd-phytoextraction programs, being a Cdhyperaccumulator species, as previous proposed by Carneiro et al (2002). The high Cd-tolerance of this species is closely related to anatomical and physiological features, including endodermal thickness, stomatal size and number, root SOD and GPX activities, and leaf GPX and CAT activities can serve as Cd-tolerance markers for this species.…”
Section: Antioxidant Enzyme Activitiessupporting
confidence: 82%
“…The shoot metal concentrations seen in Pfaffia glomerata classified the species as a Cd-hyperaccumulator, as previously reported by Carneiro et al (2002). Although the BCF is more important than shoot concentrations per se when evaluating the phytoremediation potential of a given species (Zhao et al, 2003).…”
Section: Antioxidant Enzyme Activitiessupporting
confidence: 65%
See 3 more Smart Citations